Application of pharmaceutical nanotechnology to the treatment of malaria (Revista Brasileira de Ciências Farmacêuticas, 2007)
In spite of living in a scientific and technological era, malaria continues to be one of the worldwide greatest health challenges. The state-of-the-art policy to keep malaria under control is expected to comprise joint-strategies, such as the vector control, fast diagnosis, therapeutic guarantee, resistance cutback, drug optimization and development of new therapeutic agents and vaccines. Nano and microcarrier systems have been receiving a special attention, including the development of strategies for carrying bioactive agents, vaccines through nanodevices, such as liposomes and nanoparticles, and microdevices, such as microparticles and microemulsions. Numerous nanosystems have already substantiated their effectiveness to optimize vaccines, insecticides, and chemotherapeutic agents applied to the control of malaria. This review is intended to explain the malaria scenario though the world, and to show the nanotechnology as a promising alternative for malaria control and treatment.